Respuesta :
using y=x+5 to substitute for y in y=-5x-1,
x+5=-5x-1
x+5x=-1-5
6x=-6
x=-1
i think its one
because if you make them equal to each other (cause theyre both y's), you only get one answer which is -1
x+5=-5x-1
x+5x=-1-5
6x=-6
x=-1
i think its one
because if you make them equal to each other (cause theyre both y's), you only get one answer which is -1
Answer: There is only ONE solution; which is: (-⅔, 4 ⅓) .
____________________________________________________
Explanation:
_____________________________________________
Given:
y = x + 5 ;
y = -5x +1 ;
How many solutions does the system have?
_____________________________________
Note: -5x + 1 = 1 − 5x
So, x + 5 = -5x + 1 ;
Add "5x" to EACH SIDE; and subtract "5" from EACH SIDE;
________________________________________________________
x + 5 + 5x − 5 = -5x + 1 + 5x − 5 ;
to get: 6x = -4 ;
Divide each side of the equation by "6" ; to isolate "x" on one side of the equation ; and to solve for "x" ;
6x / 6 = -4/6 ;
x = -⅔ ;
There is only one solution.
Let us double check by plugging this value for "x" into EACH equation; to see if the same value for "y" holds true:
______________________________________
First equation:
y = x + 5;
y = (-2/3) + 5 = 5 − ⅔ = 15/3 − 2/3 = (15 − 2) / 3 = 13/3;
_____________________________________________________
So; in the second equation, does "y = 13.3 ; when "x = -⅔ " ?
y = -5x + 1 ;
______________________
y = -5*(-⅔) + 1 = (-5/1)*(-2/3) + 1 = (-5*-2) /(1*3) + 1 ;
= 10/3 + 1 = 10/3 + 3/3 = (10 + 3) / 3 = 13/3 ;
_________________________________________
Yes! So; there is only ONE solution.
x = -⅔ ; y = 13/3 ; 13/3 can be written as: "4 ⅓",
__________________________________________
So; the answer is: There is only ONE solution; which is:
(-⅔, 4 ⅓) .
__________________________________________
____________________________________________________
Explanation:
_____________________________________________
Given:
y = x + 5 ;
y = -5x +1 ;
How many solutions does the system have?
_____________________________________
Note: -5x + 1 = 1 − 5x
So, x + 5 = -5x + 1 ;
Add "5x" to EACH SIDE; and subtract "5" from EACH SIDE;
________________________________________________________
x + 5 + 5x − 5 = -5x + 1 + 5x − 5 ;
to get: 6x = -4 ;
Divide each side of the equation by "6" ; to isolate "x" on one side of the equation ; and to solve for "x" ;
6x / 6 = -4/6 ;
x = -⅔ ;
There is only one solution.
Let us double check by plugging this value for "x" into EACH equation; to see if the same value for "y" holds true:
______________________________________
First equation:
y = x + 5;
y = (-2/3) + 5 = 5 − ⅔ = 15/3 − 2/3 = (15 − 2) / 3 = 13/3;
_____________________________________________________
So; in the second equation, does "y = 13.3 ; when "x = -⅔ " ?
y = -5x + 1 ;
______________________
y = -5*(-⅔) + 1 = (-5/1)*(-2/3) + 1 = (-5*-2) /(1*3) + 1 ;
= 10/3 + 1 = 10/3 + 3/3 = (10 + 3) / 3 = 13/3 ;
_________________________________________
Yes! So; there is only ONE solution.
x = -⅔ ; y = 13/3 ; 13/3 can be written as: "4 ⅓",
__________________________________________
So; the answer is: There is only ONE solution; which is:
(-⅔, 4 ⅓) .
__________________________________________